Efetividade da massagem percussiva na intensidade da fadiga e dor muscular do quadríceps, torque muscular dos extensores de joelho e na altura do salto vertical: protocolo de ensaio clínico randomizado cruzado. - Oliveira Caetano, Raphael; Soares Alves, Bruno; Silveira Pires, Francisco; de Oliveira Lauria, Fernanda; Vergara Marques, Isabela; Nicolau Gomes, Ana Carolina; Simões Fonseca, Diogo; Carvalho Felício, Diogo (ConScientiae Saúde, 2025)
Introduction: Various methods have been employed to optimize post-training recovery, among which massage is prominent. Recently, percussive massage has gained attention; however, preliminary results are conflicting, and there are reports of adverse effects. Objectives: This study aims to investigate the effectiveness of percussive massage on muscle fatigue intensity, muscle pain intensity, knee extensor torque, and vertical jump height. Methodology: A randomized crossover clinical trial (RBR-33dz538) with evaluator blinding will be conducted. Active participants aged 18 to 40 years will be included, while those with self-reported musculoskeletal pain in the hip or knee at baseline will be excluded. Participants will be randomized to receive percussive massage (AVANUTRI®) and passive recovery following a knee extensor fatigue induction protocol. Muscle fatigue intensity and quadriceps muscle pain intensity during squatting (Numerical Visual Analog Scale), knee extensor muscle torque (PHYSIOCODE F-01® dynamometer), and vertical jump height (Baiobit® inertial sensor) will be assessed. Discussion: It is anticipated that percussive massage will improve both objective and subjective test outcomes. This research may contribute to evaluating the effectiveness of percussive massage, which is widely used but still lacks robust scientific evidence.